Overtraining and burnout in elite athletes: When physiology meets psychology - Lemyre, P.-N.; Roberts, G. C.; Treasure, D.; Stray-Gundersen, J.; Matt, K. (Pre-olympic Congress 2004. Thessaloniki, Grécia. de 6 a 11 de Agosto de 2004, 2004)
The aim of this study was to look at how motivation and hormonal changes in elite athletes can better predict together burnout at season's end. Overtraining and burnout share diagnosis characteristics like performance loss, fatigue, exhaustion, and mood disturbance. However, when an athlete is overtrained, motivation remains, whereas the burned out athlete will typically show signs of sport devaluation and express cynicism. Chronic stress and overtraining are expected to cause increases in basal cortisol, a possible indication of metabolic problems. Variation in basal cortisol was hypothesized to predict burnout when combined with maladaptive motivational dispositions. Summary: Basal cortisol and achievemtn goals were found to be strong predictors of burnout in elite swimmers. Results demonstrate the value of a multi-dimensional approach to understand overtraining and burnout in elite athletes.